Controlled expansion stent grafts versus legacy stent grafts for transjugular intrahepatic portosystemic shunt - Fonseca, Afonso (2025)
Purpose: Assess incidence of hepatic encephalopathy (HE) after transjugular intrahepatic portosystemic shunt (TIPS) in patients treated with 8-10 mm Controlled Expansion diameter VIATORR® (VCX) versus 10 mm diameter first-generation VIATORR® (Legacy) stent-grafts. Materials and methods: Single-centre retrospective study (January 2015 to March 2024), including 132 adult patients with cirrhosis treated with TIPS due to complications of portal hypertension. Outcomes included post-TIPS new onset overt HE, ascites response, re-bleeding, mortality and portal pressure gradient (PPG) before and after TIPS. Comparisons used Chi square and Fisher´s exact test for categorical variables and Student´s t test or Mann–Whitney test for quantitative variables. Results: Indication for TIPS was refractory ascites (n = 82) and variceal bleeding (n = 50). The VCX group (n = 85) and the Legacy group (n = 47) had similar new onset overt HE: 37% (31/85) vs 43% (20/47), respectively (p = 0.31); mortality rates (34% [29/85]) vs 39% [18/47], respectively, p = 0.57) and re-bleeding (17% [6/35] vs 20% [3/15], respectively, p = 1.00). Median PPG reduction after TIPS was 10 mmHg (7 – 13) in the VCX group and 12 mmHg (9 – 15) in the Legacy group (p = 0.02). Subgroup analysis revealed post TIPS overt HE rate of 38% (19/50) in the VCX group vs 53% (17/32) in the Legacy group (p = 0.13), with refractory ascites as an indication. Shunt dysfunction rate was 7% (6/85) in the VCX group (stent thrombosis n = 6, stenosis or malpositioning n = 0) and 0% (0/47) in the Legacy group (p = 0.09). Conclusion: VCX stent grafts induce an immediate lower PPG reduction, which might lead to more stent dysfunctions, but also to a reduction in post-TIPS HE.